2016
DOI: 10.1186/s40478-016-0369-5
|View full text |Cite
|
Sign up to set email alerts
|

Systemic inflammation disrupts oligodendrocyte gap junctions and induces ER stress in a model of CNS manifestations of X-linked Charcot-Marie-Tooth disease

Abstract: X-linked Charcot-Marie-Tooth disease (CMT1X) is a common form of inherited neuropathy resulting from different mutations affecting the gap junction (GJ) protein connexin32 (Cx32). A subset of CMT1X patients may additionally present with acute fulminant CNS dysfunction, typically triggered by conditions of systemic inflammation and metabolic stress. To clarify the underlying mechanisms of CNS phenotypes in CMT1X we studied a mouse model of systemic inflammation induced by lipopolysaccharide (LPS) injection to c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
27
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 30 publications
(28 citation statements)
references
References 75 publications
(114 reference statements)
0
27
0
Order By: Relevance
“…A major question raised by these studies, and requiring further investigation, is whether the connexin loss leads to a direct reduction of BBB/BSCB integrity, which in turn promotes an increased inflammatory response, or whether loss of connexins promotes a more vigorous intrinsic brain immune response, as indicated by the abnormal cytokine responses in GJ deficient mice, which secondarily causes BBB/BSCB disruption. Previous studies in brains of mice deficient in oligodendrocyte GJs demonstrated activation of immune cells (Georgiou et al, 2017;Markoullis, Sargiannidou, Gardner, et al, 2012;Olympiou et al, 2016;Schiza et al, 2015;Tress et al, 2011) and upregulation of pro-inflammatory genes expressed by both microglia and astrocytes (Wasseff & Scherer, 2015). Some evidence for a pro-inflammatory environment in the CNS resulting from loss of oligodendrocyte connexins has been shown in Cx32/Cx47 double KO mice (Georgiou et al, 2017;Schiza et al, 2015;Wasseff & Scherer, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…A major question raised by these studies, and requiring further investigation, is whether the connexin loss leads to a direct reduction of BBB/BSCB integrity, which in turn promotes an increased inflammatory response, or whether loss of connexins promotes a more vigorous intrinsic brain immune response, as indicated by the abnormal cytokine responses in GJ deficient mice, which secondarily causes BBB/BSCB disruption. Previous studies in brains of mice deficient in oligodendrocyte GJs demonstrated activation of immune cells (Georgiou et al, 2017;Markoullis, Sargiannidou, Gardner, et al, 2012;Olympiou et al, 2016;Schiza et al, 2015;Tress et al, 2011) and upregulation of pro-inflammatory genes expressed by both microglia and astrocytes (Wasseff & Scherer, 2015). Some evidence for a pro-inflammatory environment in the CNS resulting from loss of oligodendrocyte connexins has been shown in Cx32/Cx47 double KO mice (Georgiou et al, 2017;Schiza et al, 2015;Wasseff & Scherer, 2015).…”
Section: Discussionmentioning
confidence: 98%
“…However, early studies demonstrated that Cx32 mutants associated with CNS phenotypes were retained in the endoplasmic reticulum and Golgi apparatus of oligodendrocytes, suggesting a toxic gain of function 39. In fact, recent studies have found that under the influence of systemic inflammation transdominant effects of mutant Cx32 on other connexins can disrupt oligodendrocyte gap junctions, although oligodendrocyte dysfunction is further exacerbated by intracellularly retained mutants (eg, Thr55Ile) 40. Nevertheless, other studies have recently observed that even mutations associated with a complete loss of Cx32 can produce CNS dysfunction 41.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, at least one case with a start codon mutation in GJB1 and documented complete loss of Cx32 expression was also associated with transient CNS manifestations, suggesting that gain-offunction effects are not necessary for the CNS manifestations of CMT1X [62]. Further studies to elucidate the consequences of GJB1 mutations, in particular in the CNS, were subsequently undertaken and discussed below [63,64].…”
Section: X-linked Charcot-marie-tooth Diseasementioning
confidence: 99%
“…In order to understand the cellular mechanisms underlying the CNS phenotypes in patients with CMT1X (above), we used a model of systemic inflammation induced by lipopolysaccharide (LSP) injection. We compared the effects of LPS-induced systemic inflammation in Cx32 KO mice expressing the T55I mutant (KO T55I) with WT and Cx32 KO mice [63]. We assumed that dominant effects of the T55I mutant might only become obvious under stress conditions that mimic the metabolic and inflammatory events leading to encephalopathy in CMT1X patients [55][56][57][58].…”
Section: Modeling Inflammation-induced Cns Manifestations Of Cmt1xmentioning
confidence: 99%